2018
DOI: 10.1021/acs.jafc.7b04905
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic Acid:Dihomo-γ-Linolenic Acid Ratio Predicts the Efficacy of Zn-Biofortified Wheat in Chicken (Gallus gallus)

Abstract: The amount of Zn absorbed from Zn-biofortified wheat material has been determined using an in vivo model of Zn absorption. The erythrocyte linoleic:dihomo -γ-linolenic acid (LA:DGLA) ratio was used as a biomarker of Zn status. Two groups of chickens (n = 15) were fed different diets: a high-Zn (46.5 μg Zn g) and a low-Zn wheat-based diet (32.8 μg Zn g). Dietary Zn intakes, body weight, serum Zn, and the erythrocyte fatty acid profile were measured, and tissues were taken for gene expression analysis. Serum Zn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 24 publications
(78 citation statements)
references
References 48 publications
(100 reference statements)
9
69
0
Order By: Relevance
“…Moreover, desaturase enzymes are coupled to the NAD (P) H-cytochrome b5 electron transferrin chain and insufficient dietary Zn intake might affect the electron transferring chain and subsequently change the activities of desaturases and their relationship with lipid status parameters [99]. Furthermore, Zn modifies cyclooxy-genase activity and it acts as a co-enzyme for ∆6 desaturase [31][32][33]39]. The link between the ∆6 desaturase and Zn has been studied both in animals and humans [32,34,35,39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, desaturase enzymes are coupled to the NAD (P) H-cytochrome b5 electron transferrin chain and insufficient dietary Zn intake might affect the electron transferring chain and subsequently change the activities of desaturases and their relationship with lipid status parameters [99]. Furthermore, Zn modifies cyclooxy-genase activity and it acts as a co-enzyme for ∆6 desaturase [31][32][33]39]. The link between the ∆6 desaturase and Zn has been studied both in animals and humans [32,34,35,39].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zn modifies cyclooxy-genase activity and it acts as a co-enzyme for ∆6 desaturase [31][32][33]39]. The link between the ∆6 desaturase and Zn has been studied both in animals and humans [32,34,35,39]. The LA:DGLA ratio has been proposed as a potentially new biomarker of Zn status as it has been demonstrated that the ratio changes in accordance to dietary Zn manipulations [32,33,39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chicken (Gallus gallus) model is physiologically relevant for estimating dietary micronutrient absorption in humans due to similarities in intestinal morphology and enteric microbiota, and has been used in numerous studies to evaluate Fe and Zn bioavailability in staple foods [35][36][37][38][39][40][41][42][43][44] . Here we utilized the chicken model to investigate the impact of NA-chelated and EDTA-chelated Fe on Fe status and gastrointestinal health when delivered alongside extracts of control and biofortified white wheat flour containing increased NA, Fe, Zn and DMA through intraamniotic administration four days prior to hatch (short-term exposure).…”
mentioning
confidence: 99%